2016
DOI: 10.1007/s11695-015-2038-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential Acute Impacts of Sleeve Gastrectomy, Roux-en-Y Gastric Bypass Surgery and Matched Caloric Restriction Diet on Insulin Secretion, Insulin Effectiveness and Non-Esterified Fatty Acid Levels Among Patients with Type 2 Diabetes

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
8
1
1
Order By: Relevance
“…Therefore, in our case, although LSG improved insulin resistance along with decreasing fat areas and improving glycemic metabolism, insulin secretion remained higher, especially in the early phase after the glucose load. This clinical feature is different from that of the patients with primary obesity in whom insulin hypersecretion is ameliorated with weight reduction after LSG (Nannipieri et al 2013;Thomas et al 2016). Because LSG increased GLP-1 (Ionut et al 2013) that enhances insulin secretion after diet (Koliaki and Doupis 2011), it is possible that, in our case, LSG could further enhance insulin secretion, although insulin hypersecretion state already existed.…”
Section: Discussioncontrasting
confidence: 54%
“…Therefore, in our case, although LSG improved insulin resistance along with decreasing fat areas and improving glycemic metabolism, insulin secretion remained higher, especially in the early phase after the glucose load. This clinical feature is different from that of the patients with primary obesity in whom insulin hypersecretion is ameliorated with weight reduction after LSG (Nannipieri et al 2013;Thomas et al 2016). Because LSG increased GLP-1 (Ionut et al 2013) that enhances insulin secretion after diet (Koliaki and Doupis 2011), it is possible that, in our case, LSG could further enhance insulin secretion, although insulin hypersecretion state already existed.…”
Section: Discussioncontrasting
confidence: 54%
“…We selected part of papers to compare the results from different regions of the world. The outcomes of studies from Asia, [9,10] Europe, [11] North America, [8] South America [4] and Oceania [12] are listed in Table 4. We found no studies from Africa.…”
Section: Discussionmentioning
confidence: 99%
“…In all three groups, palmitic acid, stearic acid, linoleic acid, DGLA, and EPA decreased after surgery, while oleic acid, arachidonic acid, and DHA levels stayed unchanged. No significant difference for oleic acid has previously been demonstrated 3 days after RYGB in two other studies that at the same time found significant decreases in both palmitic acid, stearic acid, and linoleic acid (Nemati et al, 2017; Thomas et al, 2016).…”
Section: Discussionmentioning
confidence: 83%